Polyaniline modified cotton fabric and preparation method thereof

Through interfacial polymerization reaction and sodium sulfosalicylate doping method, the conductive properties of polyaniline cotton fabrics are improved, the problem of limited conductivity in the prior art is solved, and its performance in various application fields is enhanced.

CN119711184APending Publication Date: 2025-03-28YANCHENG INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411756779.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In the prior art, the conductive properties of polyaniline cotton fabrics are limited and it is difficult to meet the needs of smart wearable, antistatic and electromagnetic shielding.

Method used

By mixing aniline and dichloromethane to form an organic phase solution, and undergoing interfacial polymerization with ammonium persulfate and sodium sulfosalicylate in an aqueous solution, polyaniline is deposited on the cotton fabric, and then doping it in the sodium sulfosalicylate solution, polyaniline modified cotton fabric with improved conductivity was prepared.

Benefits of technology

It significantly improves the conductive properties of polyaniline cotton fabrics and enhances its application potential in the fields of smart wearable, antistatic and electromagnetic shielding.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119711184A_ABST
    Figure CN119711184A_ABST
Patent Text Reader

Abstract

The invention discloses a polyaniline modified cotton fabric and a preparation method thereof, polyaniline is deposited on the cotton fabric through interfacial polymerization under the action of sodium sulfosalicylate, then the cotton fabric is soaked in a sodium sulfosalicylate solution to obtain the polyaniline modified cotton fabric, and the influence of the aniline dosage on weight increment and conductivity of the polyaniline modified cotton fabric is explored. The influence of the concentration of the sodium sulfosalicylate solution for soaking the cotton fabric on the conductivity of the polyaniline modified cotton fabric is researched, and the polyaniline modified cotton fabric prepared by the method has excellent electromagnetic shielding and conductivity and has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cotton fabrics, and in particular relates to a polyaniline modified cotton fabric and a preparation method thereof. Background Art

[0002] Since the successful synthesis of "aniline black" in the 1860s, polyaniline has become known to people. It was not until the discovery of the conductive polymer polyacetylene in the 1970s that scientists began to gradually conduct in-depth research on conductive polymers. In the mid-1980s, MacDiarmid et al. found that polyaniline can be doped to obtain a highly conductive state, which is called "emeraldine". Polyaniline is a structure in which benzene and quinone rings coexist in different proportions. Its structure has three easily achievable oxidation states, namely, fully reduced cryptoemeraldine, semi-oxidized emeraldine and fully oxidized peraniline black, among which emeraldine has the highest conductivity state.

[0003] Compared with other inherently conductive polymers, polyaniline has a more diverse structure. Polyaniline can be doped with protons or p-type, so it generates amino salts. The most common method for synthesizing polyaniline is through chemical oxidation polymerization of aniline monomers in an acidic solution. The chemical polymerization method is simple in process and suitable for mass production. It is the main commercial method for producing polyaniline. In the chemical polymerization method, an oxidant with oxidation ability is indispensable. In many studies, the most widely used chemical oxidant is ammonium persulfate. Through spectral research, it is known that due to the strong oxidation ability of ammonium persulfate, the polymer produced at the beginning is completely oxidized peraniline black, but when the oxidant is completely consumed, the remaining aniline monomer will reduce the peraniline black to obtain the final product-green emeraldine salt. Conductive polymer polyaniline has readily available raw materials, simple synthesis process, and good conductivity. Through research, it is found that polyaniline can be used in smart wearables, antistatic, electromagnetic shielding and other fields, and Kuhn et al. proposed that conductive fabrics can be successfully prepared by depositing conductive polyaniline on fabrics. The conductive properties of polyaniline cotton fabrics in the prior art are limited. Therefore, it is of great significance to further improve the conductive properties of polyaniline cotton fabrics. Summary of the invention

[0004] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0005] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0006] Therefore, the object of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing polyaniline modified cotton fabric.

[0007] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0008] Aniline and dichloromethane are mixed evenly in a volume ratio of 1 to 4:85 to obtain an organic phase solution;

[0009] ammonium persulfate and sodium sulfosalicylate are added to deionized water and mixed to obtain an aqueous phase solution;

[0010] The washed and dried cotton fabric is placed in an organic phase solution, and an aqueous phase solution is added dropwise to perform an interfacial polymerization reaction, and then the cotton fabric is taken out, washed and dried to obtain a dark green fabric;

[0011] The dark green cotton fabric is immersed in a sodium sulfosalicylate solution with a concentration of 50 to 200 g / mL, doped, and then washed and dried to obtain a polyaniline-modified cotton fabric.

[0012] The molar ratio of the aniline, ammonium persulfate and sodium sulfosalicylate in the aqueous solution is 1-1.2:0.8:0.8.

[0013] As a preferred solution of the method for preparing polyaniline-modified cotton fabric of the present invention, the volume ratio of aniline to dichloromethane is 2-4:85.

[0014] As a preferred solution of the method for preparing polyaniline-modified cotton fabric of the present invention, the volume ratio of aniline to dichloromethane is 3.5-4:85.

[0015] As a preferred embodiment of the method for preparing polyaniline-modified cotton fabric of the present invention, the molar ratio of aniline, ammonium persulfate and sodium sulfosalicylate in the aqueous solution is 1-1.1:0.8:0.8.

[0016] As a preferred embodiment of the method for preparing polyaniline-modified cotton fabric of the present invention, the concentration of ammonium persulfate in the aqueous solution is 20-83 g / L.

[0017] As a preferred embodiment of the method for preparing polyaniline-modified cotton fabric of the present invention, the concentration of sodium sulfosalicylate in the aqueous solution is 24-100 g / L.

[0018] As a preferred solution of the method for preparing polyaniline-modified cotton fabric of the present invention, the volume ratio of the organic phase solution to the aqueous phase solution is 1-1.2:1.

[0019] As a preferred solution of the method for preparing polyaniline-modified cotton fabric of the present invention, the interfacial polymerization reaction is carried out in a sealed environment at a temperature of 0 to 5° C. for 24 to 48 hours.

[0020] As a preferred solution of the method for preparing polyaniline-modified cotton fabric of the present invention, the concentration of the sodium sulfosalicylate solution used for soaking the dark green cotton fabric is 100-150 g / mL.

[0021] As a preferred embodiment of the method for preparing polyaniline-modified cotton fabric of the present invention, the soaking time is 4 to 6 hours.

[0022] Beneficial effects of the present invention:

[0023] In the present invention, polyaniline is deposited on cotton fabric by interfacial polymerization under the action of sodium sulfosalicylate, and then the fabric is soaked in a sodium sulfosalicylate solution to obtain a polyaniline-modified cotton fabric. The effects of the amount of aniline on the weight gain and conductivity of the polyaniline-modified cotton fabric are investigated, and the effect of the concentration of the sodium sulfosalicylate solution used for soaking the cotton fabric on the conductivity of the polyaniline-modified cotton fabric is investigated. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0025] Figure 1 These are SEM photos of the cotton fabric in Comparative Example 1 of the present invention and the PANI cotton fabric in Example 1.

[0026] Figure 2 FTIR spectra of the cotton fabric in Comparative Example 1 of the present invention and the PANI cotton fabric in Example 1.

[0027] Figure 3 The XRD spectra of the cotton fabric in Comparative Example 1 of the present invention and the PANI cotton fabric in Examples 1-3 are shown.

[0028] Figure 4 These are appearance photos of the cotton fabric in Comparative Example 1 of the present invention and the PANI cotton fabric in Examples 1-4.

[0029] Figure 5 This is a graph showing the effect of aniline dosage on the weight gain of PANI cotton fabric in Examples 1-4 of the present invention and Comparative Example 1.

[0030] Figure 6Graph showing the effect of aniline dosage on the resistivity and conductivity of PANI cotton fabric in Examples 1-4 of the present invention and Comparative Example 1.

[0031] Figure 7 This is a graph showing the effect of aniline dosage on the electromagnetic shielding effectiveness of PANI cotton fabric in Examples 1-4 of the present invention and Comparative Example 1.

[0032] Figure 8 This is a graph showing the effect of the concentration of the sodium sulfosalicylate solution used for soaking on the resistivity and conductivity of PANI cotton fabric in Example 5 of the present invention.

[0033] Fig. 9 This is a graph showing the effect of aniline dosage on the weight gain of PANI cotton fabric that has not been soaked in sodium sulfosalicylate solution in Comparative Example 2 of the present invention.

[0034] Fig.10 This is a graph showing the effect of aniline dosage on the resistivity and conductivity of PANI cotton fabric that has not been soaked in sodium sulfosalicylate solution in Comparative Example 3 of the present invention.

[0035] Fig.11 This is a graph showing the effect of aniline dosage on the weight gain of PANI cotton fabric prepared using hydrochloric acid solution in Comparative Example 3 of the present invention.

[0036] Fig.12 This is a graph showing the effect of aniline dosage on the resistivity and conductivity of PANI cotton fabric when hydrochloric acid solution is used in Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0037] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0038] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0039] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0040] In the present invention, the cotton fabric is weighed before and after finishing, and the weight gain rate WGR of the cotton fabric is calculated as shown in the following formula.

[0041]

[0042] Where: W1——cotton fabric weight, g; W2——PANI cotton fabric weight, g.

[0043] The present invention adopts the four-probe method to measure the resistivity and conductivity of PANI cotton fabric, and the specific steps are as follows:

[0044] The resistivity and conductivity of PANI cotton fabric were tested using RTS-8 four-probe tester. The current range was 100μA, and the resistivity and conductivity were determined according to the thickness of the PANI cotton fabric. The test was performed 5 times at different locations and the average value was taken.

[0045] Example 1

[0046] This embodiment provides a method for preparing polyaniline modified cotton fabric.

[0047] Dissolve 3.5 mL of aniline in 85 mL of dichloromethane at a volume ratio of 3.5:85, and stir evenly to obtain an organic phase solution;

[0048] 6.12 g of ammonium persulfate and 7.36 g of sodium sulfosalicylate were added to 85 mL of deionized water and ultrasonicated for 30 min to obtain an aqueous solution. The molar ratio of aniline, ammonium persulfate and sodium sulfosalicylate in the aqueous solution was 1:0.8:0.8, the concentration of ammonium persulfate was 72 g / L, and the concentration of sodium sulfosalicylate was 87 g / L.

[0049] 0.856 g of cotton fabric with a diameter of 10 cm was ultrasonically cleaned with deionized water and anhydrous ethanol, dried at 60°C, placed in an organic phase solution, and the aqueous phase solution was added dropwise. The sealed interface was polymerized at 5°C for 24 h, and the cotton fabric was taken out, washed with deionized water until the washing liquid was colorless, and dried at 60°C to obtain a dark green cotton fabric, which was stored at low temperature;

[0050] 10 g of sodium sulfosalicylate was added to 200 mL of deionized water at a concentration of 50 mg / L, and dissolved by ultrasonication to obtain a sodium sulfosalicylate solution. Dark green cotton fabric was immersed in the sodium sulfosalicylate solution for 4 h, doped, taken out, washed, and vacuum dried at 40°C to obtain polyaniline-modified cotton fabric (PANI cotton fabric).

[0051] Comparative Example 1

[0052] This comparative example directly uses the cotton fabric in Example 1 that has been ultrasonically cleaned with deionized water and anhydrous ethanol and dried at 60°C.

[0053] Figure 1The SEM photos of the cotton fabric in Comparative Example 1 and the PANI cotton fabric in Example 1, wherein (a) and (b) are the cotton fabrics in Comparative Example 1, and (c) and (d) are the PANI cotton fabrics in Example 1. It can be seen that the cotton fiber has a natural twist and a smooth surface structure. There are slight fine marks and a large number of tiny spherical particles on the surface of the PANI cotton fiber, which is due to the addition of sodium sulfosalicylate, which forms hydrogen bonds with aniline to form a spherical structure. The PANI particles are honeycomb-shaped, unevenly arranged, and have a large number of agglomerations, forming a tight structure. This continuous structure is more conducive to improving the conductivity and other properties of the PANI cotton fabric.

[0054] Figure 2 FTIR spectra of the cotton fabric in Comparative Example 1 and the PANI cotton fabric in Example 1. It can be seen that the cotton fabric shows a characteristic absorption band of cellulose, 3340 cm -1 The stretching vibration absorption peak of OH is 2908cm -1 The stretching vibration absorption peak of CH is 1429 cm -1 The bending vibration absorption peak of -CH2- is 1315cm -1 The in-plane bending vibration absorption peaks of CH are at 1161 and 1107 cm -1 The C-OH stretching vibration absorption peak is 1055 cm -1 The absorption peak of COC stretching vibration is at 3240cm. The overall intensity of the absorption peak of PANI cotton fabric is weakened, indicating that hydrogen bonding force is generated between polyaniline and cellulose, resulting in a weakening of the absorption peak intensity. -1 The peaks at 2902 cm are the stretching vibration absorption peaks of OH in cotton and NH in polyaniline. -1 The stretching vibration absorption peak of CH in raw cotton and polyaniline is 1673 cm -1 The peak at 1584 cm is the stretching vibration absorption peak of the C=C and C=N double bonds in polyaniline. -1 The absorption peak at 1476 cm is the skeleton vibration absorption peak of the benzene ring in polyaniline. -1 The bending vibration absorption peak of -CH2- in raw cotton is 1304cm -1 The absorption peaks of the in-plane bending vibration of CH in raw cotton and polyaniline are 1225 cm -1 and 1111cm -1 The peak at 1026 cm is the stretching vibration absorption peak of C-OH in raw cotton. -1 The stretching vibration absorption peak of COC is shown in Figure 2. It can be seen that the PANI cotton fabric contains the characteristic absorption peaks of polyaniline and cotton, indicating that the PANI cotton fabric was successfully prepared.

[0055] Example 2

[0056] The difference between this embodiment and embodiment 1 is that the molar ratio of aniline, ammonium persulfate and sodium sulfosalicylate in the aqueous solution is maintained at 1:0.8:0.8, the amounts of aniline, ammonium persulfate and sodium sulfosalicylate in the aqueous solution are adjusted to 1.5 mL, 2.63 g and 3.16 g, respectively, the volume ratio of aniline to dichloromethane is 1.5:85, and the other steps are the same as those in embodiment 1 to prepare polyaniline-modified cotton fabric.

[0057] Example 3

[0058] The difference between this embodiment and embodiment 1 is that the molar ratio of aniline, ammonium persulfate and sodium sulfosalicylate in the aqueous solution is maintained at 1:0.8:0.8, the amounts of aniline, ammonium persulfate and sodium sulfosalicylate in the aqueous solution are adjusted to 2.5 mL, 4.376 g and 5.27 g, respectively, the volume ratio of aniline to dichloromethane is 2.5:85, and the other steps are the same as those in embodiment 1 to prepare polyaniline-modified cotton fabric.

[0059] Figure 3 The XRD spectra of the fabrics in Examples 1-3 and Comparative Example 1 show that the PANI cotton fabric has diffraction peaks at 14.9°, 16.5°, 22.6° and 33.8°, which are consistent with the characteristic peaks of the cotton fabric. There is no obvious shift, nor does it have new characteristic peaks. This may be because the adsorption amount of PANI on the cotton fabric is large, and the deposition is relatively uniform, and some of the compounds that can be crystallized are wrapped in PANI. It can be seen that the polyaniline modification does not change the main crystal structure of the cotton fabric.

[0060] Example 4

[0061] The difference between this embodiment and embodiment 1 is that the molar ratio of aniline, ammonium persulfate and sodium sulfosalicylate in the aqueous solution is maintained at 1:0.8:0.8, the amount of aniline is adjusted to 1, 2, 3, and 4 mL, respectively, the amount of ammonium persulfate and sodium sulfosalicylate in the aqueous solution is adjusted accordingly, the volume ratio of aniline to dichloromethane is 1:85, 2:85, 3:85, and 4:85, respectively, and the other steps are the same as in embodiment 1 to prepare polyaniline-modified cotton fabric.

[0062] The properties of the polyaniline modified cotton fabrics of Comparative Examples 1-4 and the cotton fabric in Comparative Example 1 were compared.

[0063] Figure 4 The appearance photos of cotton fabric and PANI cotton fabric with different aniline dosages are shown in Figure 1. It can be seen that the cotton fabric is white, and the PANI cotton fabric gradually changes from blue to green, indicating that the PANI cotton fabric was successfully prepared.

[0064] When the amount of aniline is 1 mL, the PANI cotton fabric is light blue. As the amount of aniline increases, the color of the PANI cotton fabric gradually darkens from light blue to dark blue and then to dark green. When the amount of aniline is less than 2 mL, the PANI cotton fabric is blue, indicating that the PANI is in a fully oxidized state and has poor conductivity; when the amount of aniline is 2 to 4 mL, the PANI cotton fabric is dark green, indicating that the PANI is in a semi-oxidized state and has good conductivity.

[0065] Figure 5 The effect of aniline dosage on the weight gain of PANI cotton fabric. It can be seen that the weight gain of PANI cotton fabric changes from a gentle increase to a significant increase with the increase of aniline dosage.

[0066] When the amount of aniline was 1 mL, the weight gain rate of PANI cotton fabric was 23.1%, the color was light blue, and there was no obvious attachment on the fabric; when the amount of aniline reached 3 mL, the fabric thickness became thicker, there were obvious attachments on the surface, and the weight gain rate began to increase significantly; when the amount of aniline reached 4 mL, the weight gain rate of PANI fabric reached 98.9%, nearly doubling the weight, proving that a large amount of polyaniline was attached to the cotton fabric.

[0067] The resistivity and conductivity of PANI cotton fabric were measured by four-probe method. Figure 6 The figure shows the effect of aniline dosage on the resistivity and conductivity of PANI cotton fabric. It can be seen that with the increase of aniline dosage, ammonium persulfate and sodium sulfosalicylate in the aqueous solution also increase proportionally, and the resistivity and conductivity of PANI cotton fabric gradually decrease and increase, respectively, and finally change slowly, indicating that the conductive properties of PANI cotton fabric gradually increase. The change of conductive properties of PANI cotton fabric with the change of aniline dosage and its appearance color change ( Figure 4 ) are consistent.

[0068] Figure 7The figure shows the effect of aniline dosage on the electromagnetic shielding effectiveness of PANI cotton fabric. It can be seen that with the increase of aniline dosage, the electromagnetic shielding effectiveness shows an upward trend, and its change law is opposite to the change of fabric surface resistivity, which shows that the loss efficiency of PANI cotton fabric to electromagnetic waves is related to the conductivity of polyaniline. The magnitude of shielding loss depends on the continuous density of the polyaniline conductive network in cotton fabric. As can be seen from the figure, when the aniline dosage is 1mL, the shielding effectiveness approaches zero. This is because polyaniline is in a fully reduced state and has poor conductivity, which leads to almost no electromagnetic shielding effectiveness of cotton fabric. However, with the increase of aniline dosage, the electromagnetic shielding effectiveness increases accordingly. When the aniline dosage is 3mL, the electromagnetic shielding effectiveness begins to improve significantly, with a value of about 6.7dB; when the aniline dosage increases to 4mL, the shielding effectiveness jumps to about 12.7dB. This is because a large amount of polyaniline is attached to the cotton fabric, the distance between the particles decreases, and they gradually contact each other to form a network, the conductivity increases, and the impedance mismatch increases, which makes the loss efficiency jump.

[0069] Example 5

[0070] This example investigates the effect of the concentration of the sodium sulfosalicylate solution used to soak the cotton fabric on the conductivity of the polyaniline-modified cotton fabric.

[0071] The difference between this embodiment and embodiment 1 is that the concentration of the sodium sulfosalicylate solution used for soaking is adjusted to 0, 50, 100, 150, and 200 g / L, and the other steps are the same as those in embodiment 1. The volume ratio of aniline and dichloromethane is 3.5:85, and the molar ratio of aniline, ammonium persulfate, and sodium sulfosalicylate in the aqueous solution is 1:0.8:0.8 to prepare polyaniline-modified cotton fabric.

[0072] Figure 8 The figure shows the effect of the concentration of sodium sulfosalicylate solution used for soaking on the resistivity and conductivity of PANI cotton fabric. It can be seen that with the increase of the concentration of sodium sulfosalicylate, the resistivity and conductivity of PANI cotton fabric first decrease and then increase, and first increase and then decrease, respectively. When the concentration of sodium sulfosalicylate is 100g / L, the conductivity of PANI cotton fabric reaches 66.67s / m.

[0073] Comparative Example 2

[0074] The difference between this comparative example and Example 1-4 is that the dark green cotton fabric is not soaked in sodium sulfosalicylate solution, and the other steps are the same as those of Example 1-4, the volume ratio of aniline and dichloromethane is 1-4:85, and the molar ratio of aniline, ammonium persulfate and sodium sulfosalicylate in the aqueous solution is 1:0.8:0.8, to prepare polyaniline-modified cotton fabric.

[0075] Fig. 9The figure shows the effect of aniline dosage on the weight gain of PANI cotton fabric that has not been soaked in sodium sulfosalicylate solution. It can be seen that the weight gain of PANI cotton fabric increases with the increase of aniline dosage. When the aniline dosage is 1-2.5mL, the weight gain does not increase significantly with the increase of aniline dosage; when the aniline dosage is 2.5-4mL, the weight gain increases significantly with the increase of aniline dosage; when the aniline dosage is 4mL, the weight gain reaches 173%. Compared with the PANI cotton fabric soaked in sodium sulfosalicylate solution, when the aniline dosage is 1-3mL, its weight gain is greater than that of the PANI cotton fabric soaked in sodium sulfosalicylate solution, indicating that the acid is successfully doped; when the aniline dosage is 3.5-4mL, its weight gain is less than that of the PANI cotton fabric soaked in sodium sulfosalicylate solution, which may be because the crystals floating on the surface of the cotton fabric are dissolved in the sodium sulfosalicylate solution, and the weight of the cotton fabric is reduced.

[0076] Fig.10 The figure shows the effect of aniline dosage on the resistivity and conductivity of PANI cotton fabric that has not been soaked in sodium sulfosalicylic acid solution. It can be seen that compared with the PANI cotton fabric soaked in sodium sulfosalicylic acid solution, the resistivity of the PANI cotton fabric that has not been soaked in sodium sulfosalicylic acid solution has increased and the conductivity has decreased, and the performance is poor. The role of the first addition of sodium sulfosalicylic acid is to provide the acidic conditions required for aniline polymerization. The use of sodium sulfosalicylic acid helps to improve the uniformity of polyaniline deposition on the fabric surface, thereby improving the conductive properties; the role of the fabric soaked in sodium sulfosalicylic acid solution is to dope the acid to further improve the conductive properties.

[0077] Under the acidic conditions provided by the sodium sulfosalicylate solution, aniline accepts proton (acid) cationization and then undergoes interfacial polymerization to generate polyaniline. The polyaniline macromolecules flocculate and deposit on the fabric surface, resulting in a large weight gain rate of the fabric. The uniformity of polyaniline deposition on the fabric surface is good, which improves the conductivity of the fabric. If aqueous polymerization is used, the weight gain rate of the fabric is not high because aniline is slightly soluble in water. The acid radical ions of sodium sulfosalicylate are larger in volume than chloride ions, and have a greater shielding effect, which reduces the flocculation rate of macromolecules. At the same time, due to the electrostatic repulsion of the polymer deposited on the fabric (the electrostatic repulsion is small when there is no deposition or little deposition), the deposition is uniform. Soaking in the sodium sulfosalicylate solution for acid doping further improves the conductivity.

[0078] Comparative Example 3

[0079] The difference between this comparative example and Example 1-4 is that the sodium sulfosalicylate in the aqueous phase solution is replaced by HCl of the same amount, that is, a hydrochloric acid solution is used in the conventional method, and the other operating steps are the same as those in Example 1-4, and the volume ratio of aniline and dichloromethane is 1-4:85, and the molar ratio of aniline, ammonium persulfate and HCl is 1:0.8:0.8, to prepare polyaniline-modified cotton fabric.

[0080] Fig.11 The figure shows the effect of aniline dosage on the weight gain of PANI cotton fabric prepared by hydrochloric acid solution. It can be seen that when hydrochloric acid solution is used, the weight gain increases with the increase of aniline dosage. When the aniline dosage increases to 3 mL, the weight gain does not change significantly. The weight gain is much lower than that of the PANI cotton fabric in Example 1.

[0081] Fig.12 The figure shows the effect of aniline dosage on the resistivity and conductivity of PANI cotton fabric when using hydrochloric acid solution. It can be seen that when using hydrochloric acid solution, the resistivity and conductivity of PANI cotton fabric are much greater and much less than those of PANI cotton fabric in Example 1, respectively. This is because compared with hydrochloric acid, sodium sulfosalicylate has a greater shielding effect, reduces the flocculation rate of macromolecules, and the polyaniline on the PANI cotton fabric is more and more uniform, and has better conductive properties.

[0082] In summary, in the present invention, polyaniline is deposited on the cotton fabric by interfacial polymerization under the action of sodium sulfosalicylate, and then the polyaniline-modified cotton fabric is obtained by soaking it in a sodium sulfosalicylate solution. The effects of the amount of aniline on the weight gain and conductivity of the polyaniline-modified cotton fabric are investigated, and the effect of the concentration of the sodium sulfosalicylate solution used for soaking the cotton fabric on the conductivity of the polyaniline-modified cotton fabric is investigated.

[0083] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A method for preparing polyaniline modified cotton fabric, characterized in that: include, Aniline and dichloromethane are mixed evenly in a volume ratio of 1 to 4:85 to obtain an organic phase solution; ammonium persulfate and sodium sulfosalicylate are added to deionized water and mixed to obtain an aqueous phase solution; The washed and dried cotton fabric is placed in an organic phase solution, and an aqueous phase solution is added dropwise to perform an interfacial polymerization reaction, and then the cotton fabric is taken out, washed and dried to obtain a dark green fabric; The dark green cotton fabric is immersed in a sodium sulfosalicylate solution with a concentration of 50 to 200 g / mL, doped, and then washed and dried to obtain a polyaniline-modified cotton fabric. The molar ratio of the aniline, ammonium persulfate and sodium sulfosalicylate in the aqueous solution is 1-1.2:0.8:0.

8.

2. The method for preparing polyaniline modified cotton fabric according to claim 1, characterized in that: The volume ratio of the aniline to the dichloromethane is 2-4:

85.

3. The method for preparing polyaniline modified cotton fabric according to claim 2, characterized in that: The volume ratio of the aniline to dichloromethane is 3.5-4:

85.

4. The method for preparing polyaniline modified cotton fabric according to claim 1, characterized in that: The molar ratio of the aniline, ammonium persulfate and sodium sulfosalicylate in the aqueous solution is 1-1.1:0.8:0.

8.

5. The method for preparing polyaniline modified cotton fabric according to claim 4, characterized in that: In the aqueous phase solution, the concentration of ammonium persulfate is 20-83 g / L.

6. The method for preparing polyaniline modified cotton fabric according to claim 4, characterized in that: In the aqueous phase solution, the concentration of sodium sulfosalicylate is 24-100 g / L.

7. The method for preparing polyaniline modified cotton fabric according to claim 1, characterized in that: The volume ratio of the organic phase solution to the aqueous phase solution is 1-1.2:

1.

8. The method for preparing polyaniline modified cotton fabric according to claim 1, characterized in that: The interfacial polymerization reaction is carried out in a sealed environment at a temperature of 0 to 5° C. for 24 to 48 hours.

9. The method for preparing polyaniline modified cotton fabric according to claim 1, characterized in that: The concentration of the sodium sulfosalicylate solution used for soaking the dark green cotton fabric is 100-150 g / mL.

10. The method for preparing polyaniline modified cotton fabric according to claim 9, characterized in that: The soaking time is 4 to 6 hours.